Pancasila Philosophy in the Phenomenon of Gender Equality of Batak Tobacommunity Perspective Patriarchiesin Dairi District - Samadam Boangmanalu; Dewi Sartika Siregar (JURNAL EDUKASI NONFORMAL, 2023)
This study aims to determine the kinship system that exists in the life of the Toba Batak nation where there has been inequality in it and this inequality is the existence of interests in inheritance rights and the existence of discrimination against women in the form of double burdens. in this study were residents around the outskirts of Lake Toba Silalahi I Village with a total of 30 people, the type of research used in this study was qualitative research with a phenomenological approach and made the entire population into a total sampling sample based on the research results obtained data that gender equality The results of the study show that the Batak tribe who adopts a patrilineal system places women in a position below men in the aspect of adat only, whereas in everyday life Batak women have had the same opportunities as men in education, employment, and position although men are still often prioritized